The Meaning of Qawwam: (Analysis of Q.S An-nisa [4]: 34 with Hudud Theory Muhammad Shahrur - Hidayah , Falakul; Erawati , Desi; Faridatunnisa , Nor (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Qawwam has been a warm discussion and has always been a debate throughout generations from the Classics to the Contemporaries. The assumption that men are absolute leader of women is an undeniable fact in the text. Meanwhile, on the one hand, this understanding sometimes laid the foundation for practices of discrimination against women. Therefore, a variety of debates, both classical and contemporary, relating to this is a discourse. This article aims to find a meeting point between the various debates. This research uses a descriptive method of analysis. Data related to the meaning of qawwam and things related to a verse will be described for later analysis using the theory of hudud (boundary threshold) of Muhammad Shahrur. The results of this analysis are expected to offer solution as a mediator of the existing debate. Based on the results of the research, it shows that the minimum limit of a male or husband can be achieved enough byining and repairing. Then on the maximum limit of the husband is to provide a living aither physical and inward.